Gas Chromatography-mass Evaluation of Terpenoids from Persian Gulf Padina tetrastromatica sp. - Shushizadeh, Mohammad Reza (Asian Journal of Pharmaceutics (AJP), 2019)
In this research work, brown algae, Padina tetrastromatica, collected from Bushehr coasts in Persian Gulf, was extracted by non-polar and polar solvents to the isolation of terpenoid compounds. For isolation of various terpenoids, n-hexane and chloroform/ethyl acetate (1:1) were used as extraction solvents, after removal of the solvents, the gas chromatography/mass spectrum spectra of the fraction were obtained. Identification of organic constituents was made by comparison of their mass spectra and retention indices with those given in the literature and authentic samples. n-hexane fraction is consisted from alpha-humulene, decane, 2-methyl-phenol, tetradecanoic acid, and hexadecanoic acid, and chloroform-ethyl acetate fraction is consisted from pentadecane, hexadecane, 2,6,10,14-tetramethyl-hexadecane, 2,6,11-trimethyl-dodecane, 1,2-benzenedicarboxylic acid, and diisooctyl ester.